FOREIGN LANGUAGE ELECTRONIC EDUCATIONAL RESOURCE DEVELOPMENT ON THE BASIS OF BLENDED LEARNING IN THE PROCESS OF INFORMATIZATION IN HIGHER EDUCATION - Dubskikh, Angelina; Kise, Olesya; Zerkina, Natalya; Butova, Anna; Bosik, Galina (Revista Inclusiones, 2020)
The increasing interest to the development and implementation of electronic educational resources in higher education is caused by a number of factors of the modern higher education system. The rapid process of informatization, reduction of face-to-face academic hours and increase of students’ independent work hours demands adaptation of learning methods and forms from a teacher to the new pedagogical reality.In this regard, the problem of methodological support improvement in the educational process is becoming urgent. The aim of the paper is to consider the features of informatization in education process at Nosov Magnitogorsk State Technical University; to underline the stages of electronic educational resources designing that is developed with the basicon principles of blended learning; to formulate the main advantages of electronic educational resources, as well as the disadvantages of its using and tasks that are solved while using electronic educational resources.The research methods were the analysis of didactic and methodological literature on the research problem, systematization and generalization in summing up the results that are relevant for the scientifically based approach formation on the electronic technologies introduction into the highereducation system.The study describes the five stages of the education informatization process, which resulted in the formation of teachers’ information and communication competence. It is shown that Informatization of education is a long-term and continuous process that requires systematic and concerned actions both from the University administration and its teachers